Regulated DNA rearrangement during sporulation in Bacillus weihenstephanensis KBAB4. Issue 2 (9th September 2013) - Abe, Kimihiro; Yoshinari, Akira; Aoyagi, Takahiro; Hirota, Yasunori; Iwamoto, Keito; Sato, Tsutomu
Summary Temperate phages can integrate their genomes into a specific region of a host chromosome to produce lysogens (prophage). During genome insertion, prophages may interrupt the gene coding sequence. In Bacillus subtilis, the sigma factor gene sigK is interrupted by a 48 kb prophage‐like element. sigK is a composite coding sequence from two partial genes during sporulation. For over two decades, however, no further examples of DNA element‐mediated gene reconstitution other than sigK have been identified in spore formers. Here we report that the gene for dipicolinic acid (DPA) synthetase β subunit spoVFB in B. weihenstephanensis KBAB4 is interrupted by a prophage‐like element named vfbin. DPA is synthesized in the mother cell and required for maintaining spore dormancy. We found that spoVFB was a composite coding sequence generated in the mother cell via chromosomal rearrangement that excised vfbin. Furthermore, vfbin caused excision after phage‐inducer treatment, but vfbin appeared to be defective as a prophage. We also found various spore‐forming bacteria in which sporulation‐related genes were disrupted by prophage‐like DNA elements. These results demonstrate the first example of a similar mechanism that affects a sporulation gene other than sigK and suggest that this prophage‐mediated DNA rearrangement is a common phenomenon in spore‐forming bacteria.